Micromicetos anemófilos de patogenicidad condicionada y biodeterioradores, en ambientes interiores del Centro Cultural de San Marcos - Méndez-Farro y Cols., Carmen Rosa (2019)
The objective of this study is to isolate and identify potentially pathogenic anemophilic micromycetes for humans and possible biodeteriorators of goods from the San Marcos Cultural Center. Two interior environments were selected, the portrait deposit (DR) and the contemporary art deposit (DAC); 48 samples were taken, 24 in each room, 6 in each station, 3 at 11.00 h and 3 at 15.00 h. The gravimetric method was used to collect the sample; for identification, cultures were made and the microculture technique was used in foil. 96 strains of anemophilic micromycetes corresponding to 12 genera were isolated. 95,83 % (92) were molds and 4,17 % (04) were yeasts; the most frequent genus was Penicillium 60,42 % followed by Cladosporium 18,75%. The highest frequency of isolations occurred in summer 45,83 %. The environment with the highest frequency of isolations was the deposit of contemporary art 63,79 %. The presence of micromycetes belonging to the genera Cladosporium, Aspergillus and Paecilomyces associated with diseases in humans was demonstrated; and of Penicillium and Cladosporium associated with the deterioration of goods of organic origin.